Interface Optimization via Fullerene Blends Enables Open‐Circuit Voltages of 1.35 V in CH3NH3Pb(I0.8Br0.2)3 Solar Cells. Issue 16 (10th March 2021) - Liu, Zhifa; Siekmann, Johanna; Klingebiel, Benjamin; Rau, Uwe; Kirchartz, Thomas
Abstract: Nonradiative recombination processes are the biggest hindrance to approaching the radiative limit of the open‐circuit voltage for wide bandgap perovskite solar cells. In addition to high bulk quality, good interfaces and good energy level alignment for majority carriers at charge transport layer‐absorber interfaces are crucial to minimize nonradiative recombination pathways. By tuning the lowest‐unoccupied molecular‐orbital of electron transport layers via the use of different fullerenes and fullerene blends, open‐circuit voltages exceeding 1.35 V in CH3 NH3 Pb(I0.8 Br0.2 )3 device are demonstrated. Further optimization of mobility in binary fullerenes electron transport layers can boost the power conversion efficiency as high as 18.9%. It is noted in particular that the V oc fill factor product is >1.096 V, which is the highest value reported for halide perovskites with this bandgap. Abstract : The potential of wide bandgap perovskite solar cells is often limited by low open‐circuit voltages. By tuning the lowest‐unoccupied molecular‐orbital of electron transport layers via the use of different fullerenes and fullerene blends, open‐circuit voltages exceeding 1.35 V in CH3 NH3 Pb(I0.8 Br0.2 )3 device without loss in fill factor leading to a high V oc FF product of 1.10 V are demonstrated.